(untitled) (Research, Society and Development, 2020)
The STS approach has brought a renewal in the form of educational practice, in which teachers and students can research together to build scientific knowledge. In this way, themes related to the experiences lived by the students provide an educational practice enriched by meanings. In the search to improve the pedagogical action, this research is considered as problematic the educative practices of teachers, from a formative process, supported by the STS approach, and aimed to analyze the relationship of the pedagogical practices with the Freirean assumptions. It was developed in a state public school, located in the city of Santa Maria / RS, for teachers working at the levels of Elementary and/or High School, mediated by pedagogical workshops. The data were collected through a questionnaire consisting of three closed questions and categorized through Content Analysis. As a result of this study, it was possible to perceive that it provided subsidies for educational practice, in the elaboration and development of activities, showing the variability of strategies and themes that were used by teachers in their pedagogical practices, and the importance of providing new opportunities for teachers. Finally, it is understood that the training process allowed the introduction of new opportunities for teachers. And that when addressing the STS approach in their practices, they considered characteristics relevant to the educational process, anchored in Freirean assumptions.